Cover, Table of Content and Editorial Team - Admint, ATBES (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
TABLE OF CONTENTS     EFFECT OF THIOPHENONE COMPOUND ON MOTILITY AND CASEINASE PRODUCTION OF AEROMONAS HYDROPHILA Pages 40-44 Ayu Ashari Margareth Sinaga, Pande Gde Sasmita Julyantotro, and Dewa Ayu Angga Pebriani   MALASSEZIA SP. INFECTION PREVALENCE IN DERMATITIS DOGS IN BADUNG AREA Pages 45-49             Putu Henrywaesa Sudipa, Ketut Tono Pasek Gelgel, and Putu Devi Jayanti   EFFECT OF DIFFERENT STOCKING DENSITIES ON THE GROWTH AND SURVIVAL RATE OF TILAPIA (OREOCHROMIS NILOTICUS) SEEDS IN BATUR LAKE FLOATING NET CAGES Pages 50-56 Hikmah Nurazizah, I Wayan Arthana, and Gde Raka Anggara Kartika   The Structure of Macrozoobenthos Community as a Bioindicator of Water Quality in Gilimanuk Bay, Jembrana Regency, Bali Pages 57-63 Yohana Christanti Ndale, I Wayan Restu, and Ni Putu Putri Wijayanti   EFFECT OF GIVING DIFFERENT DOSES OF VITAMIN E IN FEED TO THE LEVEL OF GONAD MATURITY OF TILAPIA (OREOCHROMIS NILOTICUS) Pages 64-68             Gunawan Tarigan, I Wayan Arthana, and Dewa Ayu Angga Pebriani   PROFILE OF LEACHATE AND SEA WATER IN THE WASTE PROCESSING AREA SUWUNG, DENPASAR, BALI Pages 69-72 Pande Kadek Ari Iswari, I Wayan Restu, and Ni Made Ernawati